2015
DOI: 10.1515/cipms-2015-0062
|View full text |Cite
|
Sign up to set email alerts
|

A botanical and pharmacological description of petasites species

Abstract: The objective of this review was to evaluate the botanical and pharmacological description of Petasites species. Petasides (butterbur) as a perennial shrub which was found in Europe and also in a parts of Asia and North America, has been widely used medicinally for centuries. At present, the main phytopharmacology uses for Petasides extracts are for prophylactic treatment of migraines, as well as an antispasmodic agent for bronchial asthma and pertussis. Furthermore, it has been used effectively in preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…To observe the effect on cell viability of Butterbur root extract we used an MTT assay based on the conversion of tetrazolium salt from oxidoreductase enzymes to insoluble formazan (colour compound) and measurement of the absorption intensity of staining as described by Mosmann [18]. MDA-MB-231, MCF-7 and L929 cells were treated with different concentrations of BE (2,4,8,40,200,250, 500, 1000 and 5000 μg/mL) for 72 h. After the incubation time 20 μL of 5 mg/mL of MTT ((3-(4,5-dimethylthiazol-2-yl)-2,5-diphe nyltetrazolium bromide) Merck, Germany) reagent were added to each well in 96-well plates. The cells were incubated for 3 h at 37 °C.…”
Section: Mtt Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…To observe the effect on cell viability of Butterbur root extract we used an MTT assay based on the conversion of tetrazolium salt from oxidoreductase enzymes to insoluble formazan (colour compound) and measurement of the absorption intensity of staining as described by Mosmann [18]. MDA-MB-231, MCF-7 and L929 cells were treated with different concentrations of BE (2,4,8,40,200,250, 500, 1000 and 5000 μg/mL) for 72 h. After the incubation time 20 μL of 5 mg/mL of MTT ((3-(4,5-dimethylthiazol-2-yl)-2,5-diphe nyltetrazolium bromide) Merck, Germany) reagent were added to each well in 96-well plates. The cells were incubated for 3 h at 37 °C.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Representatives of genus Petasites contain high levels of bioactive substances with promising therapeutic potential [1]. Studies have shown that they exhibit anti-inflammatory, analgesic, antioxidant, diuretic, anti-spasmodic, anti-tumour and other activities [1,2]. Among many secondary metabolites of the species of this genus such as polyphenol acids, flavonoids, lignans, thanines and small concentrations of pyrrolizidine alkaloids, the pharmacological effects are mainly attributed to eremophilane type sesquiterpenes and sesquiterpene lactones [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary inflorescence is a flower head, while the secondary inflorescence is a raceme. The petioles are light grey, fuzzy and hollow and the plant possesses thick rhizomes (Sakai et al 2008;Tys et al 2015).…”
Section: Petasites Japonicusmentioning
confidence: 99%
“…Moreover, its effects on chronic diseases have been demonstrated, suggesting its utility as a functional food. Studies have reported the physiological functions of P. hybridus ; ( 14 , 15 ) however, to the best of our knowledge, no review articles have particularly focused on the physiological functions of P. japonicus . Therefore, in this review, the functions of P. japonicus are summarized, as they may be useful for the development of potential functional foods.…”
Section: Introductionmentioning
confidence: 99%